Northwest History. Alaska, United States. (1936)
Alaska Highways Lead To Increase In Motor Vehicles. (Alaska Highways Lead to Increase In Motor Vehicles JUNEAU, Alaska—Although most persons would exepect an annual the number of dog-teams the fact that there has been a substantial increase in the number of motor vehicles in the territory may be surprising to some. There were 502 more automobiles —pleasure cars and trucks included —licensed in 1936 than in 1935, according to the annual report of Oscar G. Olson, territorial treasurer. 3369 Vehicles Listed This raised the total number of pleasure cars in use in Alaska to 2435 and the number of trucks to 927—3362 cars in all. Juneau led all other territorial cities with 215 trucks and 557 pleasure cars. Fairbanks, in the interior, was second with 166 trucks and ,408. pleasure cars; Ketchikan, first Alaskan port of entry, was third with 136 trucks,' 377 pleasure cars, while Anchorage, to the westward, was fourth, boasting 108 trucks and 332 pleasure vehicles. Reason for this increase is interpreted here as reflecting improved economic conditions, as well as a response to additional automobile highways being constructed by the Federal Government and the territory. Highway Completed For several years there were only three cities in the whole territory of more than 500,000 square miles that were connected by road. These were Valdez, Fairbanks, and Circle over the 370-mile Richardson highway. In September of this year the new 86-mile Fairbanks-Livengood highway was completed, and earlier the 40-mile Anchorage-Palmer (Mata- nuska valley) road was finished, giving greater inter-community motorcar connection. One reason for Juneau's topping the list was seen as due to completion of the Juneau-Douglas bridge late in 1935. There is also a good stretch of road, out to the colorful Mendenhall glacier. There are 26 population centers in Alaska where there are automobiles today.